A bionic strategy for addressing scale-span issues in all-carbon electrocatalytic systems. (10th August 2017) - Liu, Yuan; Guo, Yanting; Li, Minjie; Wang, Liang; Geng, Bijiang; Chen, Zhiwen; Li, Zhen; Pan, Dengyu
Graphical abstract: Highlights: A scale-span electrocatalytic system was designed via a bionic strategy. Highly edge-active, N and O co-doped GQDs are used as the electrocatalyst. A mesh carbon network is to address the scale-span transport and diffusion issues. All-carbon system exhibits ultrahigh electrocatalytic activities in DSSC systems. Abstract: We report the rational design of an all-carbon and all-scale electrocatalytic system with ultrahigh electrocatalytic activity outperforming Pt-based electrodes by quantum mechanics calculations and bionics. According to the calculations, N and O co-doped graphene quantum dots (N-O-GQDs) could offer an ultrahigh atomic ratio of high-activity edge defects (N-C + -O, O-C +, and N-C + ) owing to the most marked edge effect and co-doping effect. To fully activate these atomic-scale defects for catalyzing the two-electron triiodide reduction applied in dye-sensitized solar cells, a mesh-capillary carbon matrix composed of carbon fibers and carbon nanotubes was constructed to well disperse the catalyst and provide fast pathways for both electron transport and electrolyte penetration/diffusion by imitating the sophisticated structure of the blood vessel system. The all-carbon ternary system exhibits high reduction potential (i.e. low overpotential) and low charge-transfer resistance, and delivers high open-circuit voltage of 0.81 V, high short circuit current density of 15.77 mA cm −2, and high conversion efficiency of 7.68%. Our study helps understand and address general and challenging scale-span issues in electrode reactions for developing more efficient and practical electrocatalytic systems merely by assembling facilely derived carbon materials as the catalyst, matrix or current collector without using other materials.